STRATEGI PEMASARAN DALAM MENINGKATKAN PENJUALAN SONGKET KAIN DI TAURAI MAYANG MENYULAM TOKO DI BUKITTINGGI - Imran Imran; Tesa Margarini Margarini (JURNAL MANAJEMEN UNIVERSITAS BUNG HATTA, 2020)
This study aims to determine the right marketing strategy in an effort to increase songket fabric sales at Mayang Taurai Embroidery shop in Bukittinggi. The analysis method in this research is to use SWOT analysis (Strong, Weakness, Opportunity, Threat), and IFE and EFE Matrix Analysis which is used as a measure of the company's internal and external environment. Then proceed with the analysis of the score weight table is a table that shows the scores on each SO Strategy, ST Strategy, WO Strategy, and WT Strategy. Based on the analysis that has been done previously, in order to increase sales in Mayang Taurai Embroidery shop in Bukittinggi, the strategy used by Mayang Taurai Embroidery shop is by utilizing SO (Strength, Opportunity) strategies, where SO strategies are strategies that utilize strengths and fill opportunities. existing, where strategies can be utilized by Mayang Taurai Embroidery shop